Estresse psicossocial no trabalho e variabilidade da frequência cardíaca na linha de base do elsa-brasil - Itamar Gusmão de Oliveira Júnior (2018)
INTRODUCTION: Job stress is associated with a greater incidence of cardiovascular diseases (CVD) and alterations in autonomic nervous system (ANS) have been pointed out as a possible pathway that explains this link. The regulation of the ANS has been assessed by Heart Rate Variability (HRV). However, studies assessing the relationship of the job stress with HRV have been limited. AIM: To investigate if job stress is associated to changes of HRV among civil servants of public universities and research institutions at the baseline of a multicenter Brazilian cohort. METHODS: A total of 9417 current workers from the ELSABrasil cohort baseline (2008-2010), free of cardiovascular diseases diagnoses, aged between 35 and 74 years (47% men, mean age: 48.5, SD: 7.1), without the use of calcium channel and beta-blockers were included. ELSA-Brasil is a multicenter cohort of civil servants from universities and research institutions of six Brazilian cities which objectives to assess the determinants of cardiovascular disease. Heart Rate Variability was estimated by a 10 minutes electrocardiogram record, conducted in rest and supine position and the following indexes were used: RMSSD, SDNN, PNN50, LF, and HF. Job stress was evaluated by the Brazilian version of the Swedish Demand-Control-Support Questionnaire and the scores in the psychological demands and job control subscales were used. The job strain was also evaluated following the Karasek's Demand-Control model: low strain job (low demand/high control), passive job (low demand/ low control), active job (high demand/ high control) and job strain (high demand/ low control). The following variables were used for adjustments: age, sex, race, educational level, nature of the occupation, body mass index, physical activity, and smoking. Generalized linear models were used, and the magnitude of the association was measured by arithmetic mean ratios (AMR) and their 95% confidence intervals. The significance level was of 0,05. After, Bonferroni correction for multiple comparisons was applied at the final model with a significance level of 0,0025. RESULTS: The job demand and the Demand-Control model were not associated with HRV. However, we found that all the quintiles of low job control (<80 percentile) was associated with a reduction of LF and SDNN parameters of HRV. Participants at the lowest quintile of job control showed a reduction of 4% (AMR: 0,96; CI 95%:0,93-0,99) in the SDNN index and of 13% (AMR:0,87; CI 95%:0,79-0,95) in the LF index when compared to the highest quintile. After applying Bonferroni correction, only the association between job control and LF index remained associated. CONCLUSION: Low job control was associated with a decrease in HRV, supporting the hypothesis that the ANS disorders may partly intermediate therelationship between job stress and CVD.KEYWORDS: ELSA-Brasil, job stress, job control, job demands, heart rate variability